RETROGRADE TALON INTRAMEDULLARY NAILS VERSUS DISTAL LOCKING PLATES IN THE MANAGEMENT OF EXTRA-ARTICULAR DISTAL FEMORAL SHAFT FRACTURES - Dündar, Abdulrahim; İpek, Deniz and Kaya, Şehmuz (Sanamed, 2023)
Introduction: Distal femoral shaft fractures are characterized by their increasing incidence and complexity, presenting a significant challenge in management. The objective of this retrospective study was to compare the clinical and radiological results of patients with extra-articular distal third femoral shaft fractures treated using either retrograde Talon Distal Fix nail or a distal femur locking plate. Material and Method: The study comprised 40 patients aged >18 years who presented at our hospital with a distal third femoral shaft fracture between January 2017 and January 2023. The patients were divided into two groups: Group TDN, treated with retrograde Talon Distal Fix nailing (n=18), and Group DLP, treated with a distal locking plate (n=22). Demographic data, follow-up period, operating time, time to union, range of motion (ROM), mechanism of injury (traffic accident, fall from height, workplace accident, gunshot injury), fracture type, complications, and surgical method were retrospectively recorded. Clinical evaluation included deformity, knee ROM, pain, and the knee total score (KSS) for walking and knee stability. Results: The mean age of the patients was 48.03±12.31 (min-max: 23-69) years, and the mean follow-up time for all patients was 15.88±2.32 (12-21) months. The mean time to union was 25.55±1.86 (22-30) weeks. Delayed union and non-union rates were similar between the research groups (P=1.000, P=0.673, respectively). Union time (weeks) and mean ROM were not significantly different between the groups (P=0.881, P=0.892, respectively). The mean operation time of the TDF group (48.78±3.94 minutes) was significantly lower than that of the DLP group (62.45±3.33 minutes) (P<0.001). The mean blood loss values of the TDF group (267.5±32.4) were significantly lower than those of the DLP group (324.1±20.2) (P<0.001). Conclusion: This study demonstrated that both retrograde talon nails and locking plates provided satisfactory clinical and radiological results in the management of distal third femoral shaft fractures. Moreover, the retrograde talon nail offered the advantages of a shorter operating time and less intraoperative blood loss.